Indonesian Public Diplomacy in Building the Country's Image Through AIYEP Program 2023-2024 - Haifa Nabila; Widiandaru Wiryawan; Risalatu Mirajiah; Agung Prija Utama (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study discusses Indonesia's public diplomacy in building a positive image of the country through the implementation of the Australia-Indonesia Youth Exchange Program (AIYEP) 2023–2024. In the context of post-pandemic globalization, public diplomacy has become a strategic instrument in communicating the values, identity, and character of the nation to the international community. The AIYEP program was analyzed using an instrumental case study qualitative approach with reference to constructivism (Wendt), nation branding (Dinnie), and public diplomacy (Cull) theories. The results of the study show that AIYEP contributes significantly to shaping positive perceptions of Indonesia through cross-cultural social interactions, the involvement of youth as informal ambassadors, and authentic narratives conveyed through direct experiences. The Ministry of Youth and Sports of the Republic of Indonesia (Kemenpora RI) plays an important role in designing cultural communication strategies, adapting post-pandemic policies, and maintaining the sustainability of diplomacy through alumni networks. This program also demonstrates the implementation of universal values such as gender equality, mutual cooperation, and social inclusion. AIYEP has proven to be a model of participatory public diplomacy that strengthens bilateral relations between Indonesia and Australia and builds Indonesia's image as an inclusive, progressive, and adaptive country in the eyes of the world.